Protein stability and folding - Feigenson, Gerald W. (Henry Stewart Talks, 2020)
Protein stability, Folding and refolding, Molecular chaperones, Motions within proteins, Protein classification by function, Protein classification by complexity
Reviewed at 2022/11/27